The effect of static, proprioceptive neuromuscular fascilitation and dynamic stretching on the activation of hamstring muscle among preadolescence / Mohd Azemir Mustafa - Mustafa, Mohd Azemir (2012)
The purpose of this study was to determine the more effective stretching method between static, PNF and dynamic stretching on the activation of hamstring muscles among preadolescence and its relationship with power. Two methods of measuring flexibility in this study employed were sit and reach test and knee flexion test. Power was measured by vertical jump test. Eighty subjects were assigned to four groups consist of static, PNF, dynamic and control group. Each of the group followed six weeks intervention program except the control group. Outcome measures were measured using pre and post test. Statistical analyses used were mixed between-within subjects ANOVA and Pearson product moment correlation. Hamstring muscle activation following interventions with PNF was superior compared to other forms of stretching (p < 0.05). Sit and reach test, F (3, 76) = 25.57; p < 0.05, knee flexion test (dominant leg), F (3, 76) = 17.414; p < 0.05, knee flexion test (non dominant leg), F(3, 76) = 22.264;p < 0.05. Relationship between sit and reach test with vertical jump, r = -0.435,/? < 0.05. As a conclusion, PNF stretching was the effective treatment compared to static or dynamic stretching, however moderate and inversed relationship between flexibility and power.